ANALISIS PENINGKATAN HASIL BELAJAR SISWA PADA MATERI RELASI DAN FUNGSI KELAS VIII-D SMP PATARUMAN DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK - Erna Kirana Solihat; Anik Yuliani; M. Afrilianto; Heti Herawati (IKIP Siliwangi, 2023)
This study aims to examine the application of a scientific approach in improving the learning outcomes on the material of Relations and Functions. The research subjects were students of class VIII-D of SMP Pataruman for the academic year 2021/2022 as many as 20 people. This research is a classroom action research conducted in two cycles consisting of four meetings. The stages of this research are: Planning, Action, Observation, and Reflection. This stage is applied repeatedly to achieve the target so that student learning outcomes experience an increase in the mastery of learning scenarios. The results showed that the application of the scientific approach was able to improve learning outcomes in each cycle. It can be shown that the average score in the first cycle was only 57.3% and increased in the second cycle to 81.85%. Student learning outcomes increased by 24.55% from the first cycle to the second cycle. So it can be concluded that the scientific approach is believed to be very effective and has a positive effect on learning that is able to improve student learning outcomes in the material Relations and Functions in class VIII-D SMP Pataruman.